Brain Sensitivity to Exclusion is Associated with Core Network Closure. Issue 1 (December 2018) - Bayer, Joseph; O'Donnell, Matthew; Cascio, Christopher; Falk, Emily
Abstract Humans are driven to pursue and preserve social relationships, and these motivations are reinforced through biological systems. In particular, individual differences in the tuning of biological systems that respond to social threats may motivate individuals to seek out differently structured social environments. Drawing on a sample of adolescent males who underwent fMRI brain imaging (n = 74) and contributed Facebook data, we examined whether biological responses to a common scenario – being excluded from an activity with peers – was associated with their social network structure. We find that neural responses during social exclusion in a priori hypothesized "social pain" regions of the brain (dACC, AI, subACC) are associated with the density and transitivity of core friendship networks. These findings suggest that neural reactivity to exclusion may be one factor that underlies network "safety". More broadly, the study shows the potential of linking social cognitive tendencies to social structural properties.